GeoSpatial semantics 4th International Conference, GeoS 2011, Brest, France, May 12-13, 2011. Proceedings - Claramunt, Christophe; Levashkin, Sergei; Bertolotto, Michela (LNCS sublibrary. SL 3, Information systems and applications, incl. Internet/Web, and HCI, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on GeoSpatial Semantics, GeoS 2011, held in Brest, France, in May 2011. The 13 papers presented together with 1 invited talk were carefully reviewed and selected from 23 submissions. The papers focus on formal and semantic approaches, time and activity-based patterns, ontologies, as well as quality, conflicts and semantic integration. They are organized in topical sections on ontologies and gazetteers, activity-based and temporal issues, models, quality and semantic similarities, and retrieval and discovery methods.